2020
DOI: 10.1108/sajbs-10-2019-0185
|View full text |Cite
|
Sign up to set email alerts
|

Ownership concentration, innovation and firm performance: empirical study in Indian technology SME context

Abstract: PurposeThis study aims to understand the influence of R&D intensity and ownership concentration on performance of Indian technology SMEs, at the intersection of “value creation” perspective of corporate governance and country cultural context in innovation.Design/methodology/approachCross-sectional data of 264 Indian technology SMEs have been employed to probe the impact of ownership and R&D intensity on market performance of the technology SMEs.FindingsThis study does not find support of individual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 109 publications
0
15
0
1
Order By: Relevance
“…According to the study in technology SMEs in India, it is confirmed that R&D intensity positively affects organizational performance [76]. The enhancement of technologies in the organization serves as a catalyst to encourage the development of strategic resources, supporting firms to succeed and maintain a competitive advantage with implications for future organizational performance [77]. One of the components of value creation in this study is knowledge creation.…”
Section: -4-structural Model and Hypotheses Testingmentioning
confidence: 52%
“…According to the study in technology SMEs in India, it is confirmed that R&D intensity positively affects organizational performance [76]. The enhancement of technologies in the organization serves as a catalyst to encourage the development of strategic resources, supporting firms to succeed and maintain a competitive advantage with implications for future organizational performance [77]. One of the components of value creation in this study is knowledge creation.…”
Section: -4-structural Model and Hypotheses Testingmentioning
confidence: 52%
“…Finally, ownership does not affect POS profitability while it affects SOS profitability only for P (private ownership). While a few scholars have ownership as an important factor in performance (Chatterjee and Bhattacharjee, 2020; Rao and Kumar, 2018), ownership as a governance structure has been seldom discussed in the context of developing countries. Ownership is a key driver in SMEs due to psychological and personal involvement aspects (Fesharaki, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The size of the enterprise plays an important role in the organization of innovative activity—Corsi et al indicate that while small enterprises characterized by a high level of flexibility relatively easily adapt innovations to introducing organizational changes in order to improve their effectiveness, large enterprises face resistance related to the acceptance and integration of innovations [ 76 ]. However, it is worth noting that high-tech SMEs engage more in product development and process innovation, whereas non-high-tech SMEs tend to associate more in organizational and market innovations [ 77 ]. A similar observation is made by Hirsch-Kreinsen, pointing out that SMEs not related to advanced technologies limit their own R&D activity, but given the limited formalization of knowledge creation and use, innovative activities usually take the form of application-oriented practical knowledge Hirsch-Kreinsen [ 45 ].…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%